RECONSTRUCTION OF ONLINE LEARNING IMPLEMENTATION PLAN BASED ON FLIPPED LEARNING MODEL MATERIAL HUMAN RESPIRATORY SYSTEM IN CLASS XI - Meishanti, Ospa Pea Yuanita; Putra, Ino Angga; Kumala, Dina Ratna (Universitas Tanjungpura, 2022)
The Covid-19 pandemic makes learning a limited, namely through online and face-to-face learning, then circulars from the government regarding simplification of lesson plans into 1 sheet with 3 main components, making it a challenge for a teacher to reconstruct the lesson plans, by adapting the current situation. The purpose of this research is to developing RPP Reconstruction Based on the Reverse Learning Model of the Human Respiratory System The material determines the feasibility of the learning design based on the learning validation questionnaire design experts, learning activities and attractiveness of lesson plans based on student responses. This research uses ADDIE a development model that has five stages, namely: 1) Analyze 2) Design 3) Develop 4) Implement, and 5) Evaluation. The subjects of this study were 2 learning design validation experts and 10 students class XI IPA. The instrument used is a learning design validation questionnaire experts and student response questionnaires. Data analysis techniques are quantitative and qualitative. The results of the validation of learning design experts that the Inspirational lesson plan for this flipped learning model obtained an average value of 91.67% feasible, and the learning implementation of 95.53% was included in the very good category. Based on these results, this RPP reconstruction can be applied to the respiratory tract system material for class XI humans and is expected to be able to The inspirational RPP reconstruction can be applied to other materials.